PENDIDIKAN AGAMA ISLAM SEBAGAI MEDIA PENCEGAHAN PERILAKU BULLYING DI SEKOLAH - Nur Hasanah Hasibuan (CV. Denasya Smart Publisher, 2025)
Bullying in schools is a serious issue affecting students' psychological and academic growth. This study aims to explore the role of Islamic Religious Education (PAI) as a medium for preventing bullying behavior. The research employs a qualitative approach through library research, analyzing various literatures on the implementation of Islamic values in shaping students' character. The findings reveal that PAI significantly contributes to bullying prevention by teaching Islamic values such as compassion, justice, and respect for others. PAI teachers play a crucial role in internalizing these values through storytelling and discussion methods. Furthermore, collaboration among teachers, students, and parents is a vital element in establishing a safe and harmonious educational environment. This study concludes that PAI is not only effective in reducing bullying incidents but also fosters students' awareness of the importance of moral values in everyday life.